Self-organized environment-sensitive inulin–doxorubicin conjugate with a selective cytotoxic effect towards cancer cells1. Issue 41 (7th May 2015) - Mauro, N.; Campora, S.; Scialabba, C.; Adamo, G.; Licciardi, M.; Ghersi, G.; Giammona, G.
<x xml:space="preserve">Abstract</x> An inulin-based copolymer bearing high dose doxorubicin (18.45 % w/w), INU-EDA-P, C-DOXO, was prepared by coupling doxorubicin with inulin though citraconylamide bridge used as pH sensitive spacer. Its smart and selective anticancer effect was proved.